Familial autosomal recessive rigid spine syndrome with neurogenic facio-scapulo-peroneal muscle atrophy. Issue 1 (January 1991) - Palmucci, L; Mongini, T; Doriguzzi, C; Maniscalco, M; Schiffer, D
Abstract : Two sisters and a first cousin presented with rigid spine and facio-scapulo-peroneal muscle atrophy. The patients belonged to a family with two first-cousin marriages. Electromyography, muscle and nerve biopsy showed neurogenic muscle atrophy without peripheral nerve involvement. Follow up did not show progression of the disease. This is the first observation of an association of neurogenic facio-scapulo-peroneal and rigid spine syndrome. The double first-cousin marriage suggests autosomal recessive inheritance.